Transfer von Expertenwissen in der Frühen Neuzeit - Gelehrte Diskurse in der volkssprachigen Praxis - Friedrich, Udo; Schumann, Eva (Universitätsverlag Göttingen, 2018)
The transfer of expert knowledge to an unlearned audience is a highly complex process. It is not only dependant on subject-specific requirements, but also on institutional and media requirements. The early modern period proves to be a time of upheaval due to book printing, during which transfer processes can be studied in a special way. The adaptation of scientific knowledge, for example of law, medicine, theology or artes , to the reception conditions of laypersons requires differentiated communication strategies that link theoretical concepts of the sciences to the requirements of technical expertise and are able to translate scholarship into practice. This volume brings together interdisciplinary contributions from the history of law, historical book studies, general rhetoric and Germanic medieval studies.